Chapter 12 Social Innovation and Collaboration Identifying and Engaging Stakeholders with Power, Purpose, Passion and Presence - Drake, Irmelin (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"This chapter explores the link between social innovation and collaboration among change agents and stakeholders. Social innovation is a field on the rise, both practically and theoretically (Cajaiba-Santana, 2014), and involves new ideas for tackling unmet social needs and solving current social problems (Mulgan et al., 2007). Even though social innovation has great potential, confronting uncertainties, risks and resistance are inevitable when engaging in this type of endeavor. Consequently, it may be challenging to mobilize key stakeholders to commit to and engage in relevant actions and collaborative processes (Marcy, 2015). The problem that will be addressed in this chapter concerns how to identify, target and mobilize key stakeholders to collaborate in social innovation initiatives. It is viewed from the vantage point of those initiating and leading social innovation efforts and aims to point out some factors that must be overcome and others that may foster constructive collaborative processes among change agents and stakeholders."